2009
DOI: 10.1159/000203356
|View full text |Cite
|
Sign up to set email alerts
|

CD34+ and CD133+ Primitive Stem Cell Expression in Peripheral Blood: Considering Gender, Age, and Smoking

Abstract: Background: The number of primitive progenitor cells (pPC) in healthy individuals, in correlation to age, gender, and smoking status, has not yet been thoroughly elucidated. Material and Methods: The pPC from a collective of 168 healthy blood donors aged 18–61 years was investigated using flow cytometric analysis. In addition, the pPC of 20 subjects were studied once a month for half a year to determine the extent of physiological variation of pPC within a single individual. Results: We demonstrated a statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Meanwhile an immunomagnetic purification technique for this antigen is available for clinical use. As shown by Reichelt et al [2], mobilization of these cells significantly differs only between sexes. Apparently in male donors more stem cells can be mobilized than in female donors.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Meanwhile an immunomagnetic purification technique for this antigen is available for clinical use. As shown by Reichelt et al [2], mobilization of these cells significantly differs only between sexes. Apparently in male donors more stem cells can be mobilized than in female donors.…”
mentioning
confidence: 78%
“…Reichelt et al [2] describe the effects of age, sex, and smoker status on mobilization of CD34+/CD133+ stem cells. CD133 antigen was first described 10 years ago and is co-expressed on approximately 75% of CD34+ hematopoietic stem cells, especially on CD34 bright cells.…”
mentioning
confidence: 99%
“…Furthermore, we analyzed the yields of primitive stem cells expressing CD34+/CD133+ antigen 16 . In our collections the CD34+/CD133+ cells yielded with 4.45 × 10 6 /kg body weight of recipient (range 2.1–12.5).…”
Section: Discussionmentioning
confidence: 99%
“…However, it was recently demonstrated that women exhibit unique vascular responses to sitting (Credeur et al., 2019; Vranish et al., 2017) and that exercise‐induced endothelial MP release differs across sex (Shill et al., 2018) and should be considered in future trials. Oral contraceptive use was not reported, as limited data suggest that there are no effects of contraceptives on baseline levels of CAC (Reichelt, Barz, & Thude, 2009; Shill et al., 2016). To examine the influence of the hormonal fluctuations on CAC or MPs (Shill et al., 2018), β‐oestradiol and progesterone were assessed and remained constant across both visits, and appear to be non‐factors.…”
Section: Discussionmentioning
confidence: 99%